Electronic Archive Design With RC4 Cryptographic Based File Security - sulistiyanto sulistiyanto; Indra Satriadi; Arif Rahman (Information Technology and Science (ITScience), 2024)
The transformation of archival document storage systems is starting to shift from physical formats that require a lot of space and storage equipment to the electronic or digital realm (often called electronic archives). This is considered to reduce the costs of procuring equipment and storage space. In line with changes in paperless storage patterns, the issue of data security and confidentiality becomes important, so that information from documents to be archived can be maintained and cannot be used by irresponsible people. One technique for securing documents digitally is to use cryptography and the algorithm chosen is Rivest cipher 4. The RC4 (Rivest Chiper 4) algorithm was chosen because the execution speed in file encryption is faster than other algorithms. This article aims to implement the RC4 algorithm into an electronic archive (e-Archieve) application. The application development method uses the waterfall method with 5 stages. The application was built using the PHP programming language and MySQL database, as well as the Rivest Cipher 4 cryptographic algorithm. The result of the application development is an electronic archive website. Every file uploaded to the server can be encrypted by the admin. Encrypted files will change to random characters like a virus. The application was tested using black box testing techniques, where all features worked as expected